Last Train to Texas : My Railroad Odyssey - Frailey, Fred W. (Railroads past and present., 2020)
"Midnight train rides, head-on freight collisions-there is never a dull moment when it comes to trains. Take a look at America's biggest railroads and meet the thunderous personalities who operate them. In Last Train to Texas, author Fred W. Frailey examines the workings behind the railroad industry and captures incredible true stories along the way. Discover how men like William "Pisser Bill" F. Thompson swerve from financial ruin, bad merger deals, and cutthroat competition, all while racking up enough notoriety to inspire a poem titled "Ode to a Jerk." Bold, savvy, and ready for a friendly brawl, the only thing louder and more thrilling than these men are the trains that they handle. Come along with Frailey as he travels the world, one railroad at a time. Whether it's riding the Canadian Pacific Railway through a blizzard, witnessing a container train burglary in the Abo Canyon, or commemorating a poem to Limerick Junction in Dublin, Ireland, Frailey's journeys are rife with excitement and the occasional mishap. Filled with humorous anecdotes and thoughtful insights into the railroading industry, Last Train to Texas is an adventure in every sense of the word"--